N-terminal prohormone brain natriuretic peptide (NT-proBNP) as a noninvasive marker for restrictive syndromes - Mady,C. (2008)
Constrictive pericarditis (CP) and restrictive cardiomyopathy share many similarities in both their clinical and hemodynamic characteristics and N-terminal prohormone brain natriuretic peptide (NT-proBNP) is a sensitive marker of cardiac diastolic dysfunction. The objectives of the present study were to determine whether serum NT-proBNP was high in patients with endomyocardial fibrosis (EMF) and CP, and to investigate how this relates to diastolic dysfunction. Thirty-three patients were divided into two groups: CP (16 patients) and EMF (17 patients). The control group consisted of 30 healthy individuals. Patients were evaluated by bidimensional echocardiography, with restriction syndrome evaluated by pulsed Doppler of the mitral flow and serum NT-proBNP measured by immunoassay and detected by electrochemiluminescence. Spearman correlation coefficient was used to analyze the association between log NT-proBNP and echocardiographic parameters. Log NT-proBNP was significantly higher (P < 0.05) in CP patients (log mean: 2.67 pg/mL; 95%CI: 2.43-2.92 log pg/mL) and in EMF patients (log mean: 2.91 pg/mL; 95%CI: 2.70-3.12 log pg/mL) compared with the control group (log mean: 1.45; 95%CI: 1.32-1.60 log pg/mL). There were no statistical differences between EMF and CP patients (P = 0.689) in terms of NT-proBNP. The NT-proBNP log tended to correlate with peak velocity of the E wave (r = 0.439; P = 0.060, but not with A wave (r = -0.399; P = 0.112). Serum NT-proBNP concentration can be used as a marker to detect the presence of diastolic dysfunction in patients with restrictive syndrome; however, serum NT-proBNP levels cannot be used to differentiate restrictive cardiomyopathy from CP.